Guidelines on the Legislative Framework for Civil Registration, Vital Statistics and Identity Management Systems - United Nations Department of Economic; Social Affairs (United Nations, 2024)
These Guidelines update and replace the 1998 Handbook on Civil Registration and Vital Statistics Systems: Preparation of a Legal Framework (United Nations publication sales no. E.98.XVII.7), which was based off previous revisions of the Principles and Recommendations. These Guidelines are intended to complement the Principles and Recommendations for Vital Statistics System, Revision 3 and the Handbooks on Civil Registration and Vital Statistics Systems. The purpose of these Guidelines on the Legislative Framework for Civil Registration, Vital Statistics and Identity Management Systems is to offer a tool for developing a strong rights-based legal framework for civil registration, vital statistics and identity management (CRVSID) systems.